Metal-doped porous carbon, preparation method and application

By adding activator and crosslinking agent to the resin-based porous carbon and performing high-temperature carbonization and melt doping treatment, metal-doped porous carbon with high conductivity and uniform structure was prepared, which solved the low conductivity and low conductivity in the prior art. High cost problem, suitable for high-performance battery materials.

CN119162484AActive Publication Date: 2024-12-20GUOKE TANMEI NEW MATERIALS (HUZHOU) CO LTD

Patent Information

Application Number
CN202411667975.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2024-12-20
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

The current resin-based porous carbon has low conductivity and high cost of preparation methods, making it difficult to achieve industrialization, and the increase in non-metal doping is limited, which affects the efficiency and storage performance of the energy storage device.

Method used

Use phenyl resin, activator and crosslinking agent to cure at 350-600°C, then pickling and reducing treatment, then carbonized and activated at high temperature in an inert atmosphere, and finally melt doping with nanometals in an inert atmosphere. and passivation treatment, metal-doped porous carbon with high electron conductivity and uniform pore structure was prepared.

Benefits of technology

It realizes high electronic conductivity and stable structural metal-doped porous carbon, which improves the compressive strength and conductivity of the material, is suitable for the secondary battery field, and reduces the preparation cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119162484A_ABST
    Figure CN119162484A_ABST
Patent Text Reader

Abstract

The invention provides metal-doped porous carbon as well as a preparation method and application thereof, and belongs to the field of battery material preparation. By adding the activating agent and the cross-linking agent, in the curing treatment process, the phenyl resin can be preliminarily carbonized under the action of the activating agent to form tiny pores with uniform structures, and is cross-linked under the combined action of the activating agent and the cross-linking agent to form a three-dimensional pore structure, so that the stability of the material structure in the subsequent treatment process is favorably maintained; and then, more active sites are further formed on the surface of the material and in pores during pickling and impurity removal, so that reduction treatment can be more uniformly carried out in the pores, and the uniformity of the pore structure is better. Furthermore, a porous carbon structure with a stable structure is formed after high-temperature carbonization treatment, defects are reduced, and a uniform and stable nano-pore structure is formed after activation treatment, so that the compressive strength of the material is improved. And in addition, during metal melting doping, metal doping is more uniform, and the conductivity can be effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material preparation, and specifically relates to metal-doped porous carbon, a preparation method and application thereof. Background Art

[0002] With the continuous development of science and technology, the demand for high-performance materials is growing. Among many new materials, porous carbon materials have attracted much attention due to their unique properties.

[0003] Porous carbon is a carbon material with a rich pore structure, which gives it high specific surface area, good adsorption performance, excellent conductivity and thermal stability. It is often used in the fields of energy, environmental protection, catalysis, adsorption separation, biomedicine, food processing, etc. Resin-based porous carbon has the advantages of easy and precise control of pore structure, high specific surface area, good chemical stability, easy processing and molding, wide source of raw materials and relatively low cost. However, the conductivity of resin-based porous carbon is low, which limits its application in fields with extremely high conductivity requirements.

[0004] The existing preparation methods of resin-based porous carbon mainly include activation method and template method. The activation method mainly uses water vapor, carbon dioxide and other gases as activators, and contacts with carbonized materials at high temperature to activate and form pores to increase the specific surface area of ​​the material, but the pore distribution of the material is uneven and the consistency is poor. Although the template method can control the pore structure in an orderly manner, the template preparation cost is high, and the prepared porous carbon needs to be etched to remove the template, resulting in high production costs and difficulty in industrialization. Among them, the template method is divided into hard template method and soft template method. The hard template method is to first synthesize a porous molecular sieve to obtain a carbon precursor, and then inject the carbon precursor into its pores to form a nano-organic / silicon composite material, and then undergo high-temperature carbonization and template etching technology to finally prepare a porous carbon material. The soft template method uses a surfactant as a template agent, and through the interaction between the surfactant and the carbon source, a porous structure is formed through self-assembly. However, there are disadvantages such as poor electronic conductivity and low compressive strength, which further damage the conductive properties of the material.

[0005] In order to improve the performance of porous carbon materials, in the existing technology, the electronic conductivity of the material can be improved by doping the material with non-metals (nitrogen, boron, phosphorus, etc.). However, the improvement in the electronic conductivity of the material is limited, and the strong activity of non-metals will cause side reactions with electrolytes, etc., reducing the initial efficiency and storage performance of the energy storage device. Summary of the invention

[0006] In view of the deficiencies in the prior art, the present invention aims to provide a metal-doped porous carbon with high electronic conductivity, uniform pore structure distribution and stable structure, a preparation method and application thereof.

[0007] One of the purposes of the present invention is to provide a method for preparing metal-doped porous carbon, the preparation method comprising the following steps: S1 first cures the phenyl resin, activator and cross-linking agent at 350-600°C, then acid washes, vacuum dries, and then introduces a reducing mixed gas for reduction treatment to obtain an intermediate material; S2, in an inert atmosphere, subjecting the intermediate material to a high-temperature carbonization treatment at 1300-1500° C., and then introducing water vapor for activation treatment to obtain porous carbon; S3: In an inert atmosphere, the porous carbon is melt-doped with nano-metal, and then passivated to obtain metal-doped porous carbon.

[0008] Preferably, the mass ratio of the phenyl resin, the activator and the cross-linking agent is 100:1-5:1-15.

[0009] Preferably, the curing treatment time is 1-6 hours.

[0010] Preferably, the phenyl resin includes one or more of phenylphenol formaldehyde resin, xylene formaldehyde resin, phenol furfural resin, benzoguanamine resin or resorcinol formaldehyde resin.

[0011] Preferably, the activator includes one or more of zinc chloride, zinc bromide and zinc nitrate.

[0012] Preferably, the cross-linking agent includes one or more of 2-methylimidazole, 4,5-dimethylimidazole, 4-formylimidazole, 2-propylimidazole or 2-phenylimidazole.

[0013] Preferably, the reducing mixed gas comprises reducing gas and nitrogen.

[0014] Preferably, the volume ratio of the reducing gas to nitrogen is 1-5:10.

[0015] Preferably, during the reduction treatment, the flow rate of the reducing mixed gas is 100-500 mL / min.

[0016] Preferably, the reduction treatment time is 1-10 hours.

[0017] Preferably, the heating rate of the high temperature carbonization treatment is 1-10°C / min.

[0018] Preferably, the holding time of the high temperature carbonization treatment is 1-6 hours.

[0019] Preferably, the temperature of the activation treatment is 1000-1200°C.

[0020] Preferably, the flow rate of the water vapor is 100-500 mL / min.

[0021] Preferably, the activation treatment time is 30-300 min.

[0022] Preferably, the mass ratio of the porous carbon to the nanometal is 100:1-10.

[0023] Preferably, the heating temperature of the melt doping is 800-1200°C.

[0024] Preferably, the holding time of the melt doping is 30-120 minutes.

[0025] Preferably, the nano-metal includes one or more of nano-magnesium, nano-lithium, nano-nickel or nano-copper.

[0026] Preferably, the particle size of the nano metal is 1-5 μm.

[0027] Preferably, during the passivation treatment, the passivation gas flow rate is 10-100 mL / min.

[0028] Preferably, the passivation treatment time is 30-300 min.

[0029] Preferably, the passivating gas comprises carbon dioxide and / or oxygen.

[0030] The second object of the present invention is to provide a metal-doped porous carbon obtained by the preparation method as described above, wherein the metal-doped porous carbon comprises 1-5wt% of metal and 95-99wt% of porous carbon.

[0031] Preferably, the specific surface area of ​​the metal-doped porous carbon is 500-3000 m 2 / g, pore volume is 0.5-3.0cm 3 / g, pore size is 1-20nm, and powder resistivity is 0.1-1Ω·cm.

[0032] A third object of the present invention is to provide an application of the metal-doped porous carbon as described above in the field of secondary batteries.

[0033] The beneficial effects of the present invention include: The present invention adds an activator and a cross-linking agent, and in the curing process, the phenyl resin can be initially carbonized under the action of the activator to form a micro-pore with uniform structure. At the same time, under the joint action of the activator and the cross-linking agent, the three-dimensional pore structure is cross-linked, which is conducive to maintaining the stability of the material structure in the subsequent treatment process and laying the foundation for the subsequent pore development. Further, the residual impurity elements are dissolved by pickling, and more active sites are formed on the surface of the material and inside the pores, which is conducive to more uniform reduction treatment inside the pores, so that the pore structure is better uniform. It is then conducive to uniformly and stably high-temperature carbonization treatment of the intermediate material to form a porous carbon structure with stable structure, reduce defects, and after activation treatment, a uniform and stable nanoporous structure is formed to improve the compressive strength of the material. The active sites of the porous carbon material described in the present invention are more and more uniform, and when the metal is further melt-doped, the metal doping is made more uniform, and while improving the conductivity, it can also further avoid causing pore blockage. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is the SEM image of the metal-doped porous carbon prepared in Example 1. DETAILED DESCRIPTION

[0035] In the following description, certain specific details are included to provide a comprehensive understanding of each disclosed embodiment. However, one skilled in the relevant art will recognize that the embodiments can be implemented without one or more of these specific details and with other methods, components, materials, etc.

[0036] Unless otherwise required herein, the words "include" and "comprising" should be interpreted as having an open and inclusive meaning, ie, "including but not limited to".

[0037] References to "one embodiment" or "an embodiment" or "a preferred embodiment" or "certain embodiments" throughout this specification are intended to include, in at least one embodiment, the specific referenced elements, structures or features described in connection with the embodiment. Thus, the phrases "in one embodiment" or "in an embodiment" or "in a preferred embodiment" or "in certain embodiments" appearing in different places throughout the specification do not necessarily all refer to the same embodiment. Furthermore, the specific elements, structures or features may be combined in any appropriate manner in one or more embodiments.

[0038] According to a first aspect of the present invention, a method for preparing metal-doped porous carbon is provided, the preparation method comprising the following steps: S1 first cures the phenyl resin, activator and cross-linking agent at 350-600°C, then acid washes, vacuum dries, and then introduces a reducing mixed gas for reduction treatment to obtain an intermediate material; S2, in an inert atmosphere, subjecting the intermediate material to a high-temperature carbonization treatment at 1300-1500° C., and then introducing water vapor for activation treatment to obtain porous carbon; S3: In an inert atmosphere, the porous carbon is melt-doped with nano-metal, and then passivated to obtain metal-doped porous carbon.

[0039] In the present invention, during the curing treatment stage, the phenyl resin, the activator and the cross-linking agent are cured at 350-600°C. On the one hand, the activator can cooperate with the cross-linking agent to promote the cross-linking between the phenyl resins to form a three-dimensional network structure, making the structure more stable; on the other hand, it can promote the low-temperature carbonization of the phenyl resin at 350-600°C to form micro-pores with uniform structure. The two cooperate with each other to form a three-dimensional network pore structure with uniform structure, which is conducive to maintaining the stability of the material structure in the subsequent treatment process and laying the foundation for the subsequent pore development.

[0040] Furthermore, the present invention dissolves the residual impurity elements by pickling and slightly etches the material, thereby exposing more active sites and introducing chemical groups such as hydroxyl and carboxyl groups. These active sites are more conducive to the subsequent reduction treatment, high-temperature carbonization treatment, activation treatment and metal melt doping of the material, which is beneficial to promoting the optimization of the material structure and the improvement of performance.

[0041] Specifically, hydrochloric acid may be used for pickling.

[0042] During the reduction treatment stage, the reduction reaction can be carried out more uniformly inside the pores, and the internal structure of the material can be adjusted to a certain extent, making the pore structure more open, forming an intermediate material with better pore structure uniformity, and further increasing the activity of the material.

[0043] In the high-temperature carbonization treatment stage, the high-temperature carbonization treatment is carried out at 1300-1500°C in an inert atmosphere. Specifically, the inert gas is nitrogen or helium. In this stage, the organic components in the material are largely decomposed, and non-carbon atoms escape in the form of gas. The formation of a three-dimensional mesh pore structure can avoid the collapse of the pore structure. It is beneficial to maintain structural stability and uniformity of pore structure.

[0044] In the present invention, the temperature of the high temperature carbonization treatment is, for example, 1300°C, 1320°C, 1350°C, 1380°C, 1400°C, 1430°C, 1450°C, 1480°C or 1500°C, and any point value between any two of the above.

[0045] During the activation treatment stage, water vapor reacts with the carbon material, etches the carbon skeleton, produces more micropores and mesopores, further increases the pore volume and specific surface area, and forms a uniform and stable nanoporous structure. At the same time, the activation treatment can also optimize the possible pore surface, which is more conducive to the metal melt doping process.

[0046] In the metal melt doping stage, the porous carbon material of the present invention has more and more uniform active sites, which makes the metal doping more uniform when further metal melt doping is performed, and while improving the conductivity, it can also further avoid pore blockage. At the same time, the interaction between nanometal and carbon can further enhance the structural stability of the material. After further passivation treatment, a passivation film is formed on the surface of the material and the pores to prevent the metal from directly contacting the electrolyte, which is conducive to reducing side reactions and ensuring the stability of material performance.

[0047] In a preferred embodiment of the present invention, the mass ratio of the phenyl resin, the activator and the cross-linking agent is 100:1-5:1-15.

[0048] In the present invention, taking phenyl resin as 100 parts by weight as an example, the activator is, for example, 1 part, 2 parts, 3 parts, 4 parts or 5 parts, the cross-linking agent is, for example, 1 part, 3 parts, 5 parts, 7 parts, 9 parts, 10 parts, 13 parts or 15 parts, and any point value between the above two parts.

[0049] When the activator is less than 1 part, the pore structure may be poorly developed due to incomplete reaction, which may increase the defects of the carbon skeleton and increase the number of closed pores, reduce the silicon storage performance of the material, and cause unstable product performance and poor consistency; when the activator is more than 5 parts, it may easily lead to excessive reaction of the material to destroy the structure, and it may also cause the pore structure to collapse during high-temperature carbonization and activation, so that the originally orderly formed pore structure will merge into large pores, destroying the consistency of the material structure. At the same time, the formed pores are larger, which reduces the compressive strength of the porous carbon; after excessive reaction, a disordered porous carbon structure is easily obtained. When nanometal is melt-doped, it is difficult for the nanometal to be evenly dispersed in the material and agglomeration is likely to occur, which may lead to unstable conductivity and local structure.

[0050] When the cross-linking agent is less than 1 part, it is easy to cause insufficient cross-linking points to be formed, and the material structure is easy to be relatively loose, and the skeleton support is insufficient. In the subsequent processing process, the material is easy to shrink and deform, resulting in unstable pore structure, and the mechanical strength of the material is easy to deteriorate. It is also easy to stabilize the carbon skeleton due to the lack of sufficient cross-linking structure, and the carbon atoms are restricted when rearranging to form a graphitized structure, and the degree of graphitization is reduced. This leads to a decrease in the conductivity of the material. When used as an electrode material, it is not conducive to the rapid transmission of electrons, and reduces the charge and discharge efficiency and power performance of the battery. When nano-metal melt doping is performed, the porous carbon structure with insufficient cross-linking is difficult to form a strong interaction with the nano-metal. It is easy to cause the nano-metal to be difficult to be evenly dispersed in the material, and it is easy to agglomerate, which reduces the effect of nano-metal on the improvement of material performance. When the cross-linking agent is greater than 15 parts, it is easy to cause excessive cross-linking to hinder pore formation, thereby affecting the subsequent processing process. Excessive cross-linking agents may also compete with other components such as activators to react, affecting the normal curing and structure formation process, resulting in the material performance cannot reach the optimal state, and increasing the uncertainty and control difficulty in the production process. At the same time, too much cross-linking agent will form more closed-pore structures, reduce the silicon storage effect of the material, and reduce the specific capacity of the material.

[0051] Preferably, the curing treatment time is 1-6 hours, for example, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours or 6 hours, and any point value between any two of the above.

[0052] In the present invention, when the curing treatment time is less than 1 hour, it is easy to cause incomplete reaction, resulting in an imperfect three-dimensional network structure and an unstable skeleton structure of the material, which affects the mechanical strength of the material. The imperfect structure and uneven composition will also affect the conductivity of the material.

[0053] Preferably, the phenyl resin includes one or more of phenylphenol formaldehyde resin, xylene formaldehyde resin, phenol furfural resin, benzoguanamine resin or resorcinol formaldehyde resin.

[0054] In the present invention, the phenyl resin is, for example, phenylphenol formaldehyde resin, xylene formaldehyde resin, phenol furfural resin, benzoguanamine resin, resorcinol formaldehyde resin, phenylphenol formaldehyde resin and xylene formaldehyde resin, phenylphenol formaldehyde resin, xylene formaldehyde resin and phenol furfural resin, or a combination of benzoguanamine resin, resorcinol formaldehyde resin and phenylphenol formaldehyde resin.

[0055] Preferably, the activator includes one or more of zinc chloride, zinc bromide and zinc nitrate.

[0056] In the present invention, the activator is, for example, zinc chloride, zinc bromide, zinc nitrate, zinc chloride or zinc bromide, or a combination of zinc bromide and zinc nitrate.

[0057] Preferably, the cross-linking agent includes one or more of 2-methylimidazole, 4,5-dimethylimidazole, 4-formylimidazole, 2-propylimidazole or 2-phenylimidazole.

[0058] In the present invention, the crosslinking agent is, for example, 2-methylimidazole, 4,5-dimethylimidazole, 4-formylimidazole, 2-propylimidazole, 2-phenylimidazole, 2-methylimidazole and 4-formylimidazole, 2-methylimidazole and 2-phenylimidazole, or a combination of 2-methylimidazole, 4-formylimidazole and 2-phenylimidazole.

[0059] Preferably, the reducing mixed gas comprises reducing gas and nitrogen.

[0060] In the present invention, the reducing gas includes one of hydrogen, carbon monoxide or ammonia. The combination of nitrogen and the reducing gas can provide a stable inert atmosphere and an effective reducing effect.

[0061] Preferably, the volume ratio of the reducing gas to nitrogen is 1-5:10, for example, 1:10, 2:10, 3:10, 4:10 or 5:10.

[0062] In the present invention, when the volume ratio of reducing gas to nitrogen is less than 1:10, it is easy to cause insufficient reduction reaction and low reaction efficiency, so that the chemical activity and performance improvement of the material are limited, and the adjustment effect on the internal structure of the material will also be weakened, making it difficult to effectively optimize the pore structure and improve the stability of the material. When the volume ratio of reducing gas to nitrogen is greater than 5:10, it is easy to cause too violent reaction, resulting in local overheating of the material, and then causing uneven changes in the material structure, which may cause the pore structure to collapse or crack; at the same time, too much reducing gas causes insufficient reaction of the reducing gas, resulting in waste of reducing gas and increasing its cost.

[0063] Preferably, during the reduction treatment, the flow rate of the reducing mixed gas is 100-500 mL / min, for example, 100 mL / min, 200 mL / min, 300 mL / min, 400 mL / min or 500 mL / min, and any value between the above two.

[0064] Preferably, the reduction treatment time is 1-10 h, for example, 1 h, 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h or 10 h, and any point value between any two of the above.

[0065] In the present invention, when the reduction treatment time is less than 1 hour, it is easy to cause incomplete reduction reaction, limited improvement on material performance, and easy to cause unstable material performance and poor consistency; when the reduction treatment time is greater than 10 hours, it is easy to change the chemical composition and structure of the material due to excessive reaction, making the structure unstable, so that the performance improvement is limited and may decline.

[0066] Preferably, the heating rate of the high temperature carbonization treatment is 1-10°C / min, for example, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min, and any point value between any two of the above.

[0067] Preferably, the holding time of the high temperature carbonization treatment is 1-6 hours, for example, 1 hour, 2 hours, 3 hours, 4 hours or 5 hours, and any value in between.

[0068] Preferably, the high temperature carbonization treatment is carried out in a tube furnace.

[0069] Preferably, the temperature of the activation treatment is 1000-1200°C, for example, it can be 1000°C, 1020°C, 1050°C, 1070°C, 1100°C, 1120°C, 1150°C, 1170°C or 1200°C, and any point value between any two of the above.

[0070] In the present invention, when the activation treatment temperature is less than 1000°C, it is difficult to fully etch the carbon skeleton to form sufficient pores, which may easily lead to insufficient pore generation and uneven pore size distribution. It may also lead to a large number of micropores that cannot be effectively formed and an unreasonable proportion of mesopores, which will also reduce the conductivity and structural stability of the material. At the same time, the temperature is too low, resulting in insufficient discharge of hydrogen, oxygen and impurities in the material, resulting in greater impedance. When the activation treatment temperature is greater than 1200°C, it is easy to cause excessive etching and structural damage. The originally formed pores may collapse or merge due to excessive reaction, causing the pore structure to lose uniformity and stability.

[0071] Preferably, the flow rate of the water vapor is 100-500 mL / min, for example, 100 mL / min, 200 mL / min, 300 mL / min, 400 mL / min or 500 mL / min, and any value between any two of the above.

[0072] Preferably, the activation treatment time is 30-300 min, for example, 30 min, 60 min, 120 min, 180 min, 240 min or 300 min, and any value between any two of the above.

[0073] Preferably, the mass ratio of the porous carbon to the nanometal is 100:1-10, for example, it can be 100:1, 100:2, 100:3, 100:4, 100:5, 100:6, 100:7, 100:8, 100:9 or 100:10.

[0074] In the present invention, when the mass ratio of porous carbon to nanometal is less than 100:1, it is difficult for nanometal to form a continuous conductive network in the porous carbon, and the effect of improving the conductivity of the material is limited, and the improvement of structural stability is not obvious; when the mass ratio of porous carbon to nanometal is greater than 100:10, nanometal particles are more likely to agglomerate during the preparation process and are difficult to be evenly dispersed in the porous carbon, which not only reduces the effective utilization rate of the nanometal, but also may cause local uneven performance. The presence of a large amount of nanometal may interfere with the formation and stability of the porous carbon skeleton. During the high-temperature melt doping process, too much nanometal may over-react with carbon, change the structural morphology of carbon, and cause defects or discontinuities in the carbon skeleton, which will reduce the mechanical strength and structural stability of the material, making the material more susceptible to rupture or damage during use, affecting its long-term performance and reliability.

[0075] Preferably, the heating temperature of the melt doping is 800-1200°C, for example, it can be 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C or 1200°C, and any point value between any two of the above.

[0076] Preferably, the holding time of the melt doping is 30-120 min, for example, 30 min, 50 min, 70 min, 90 min, 100 min or 120 min, and any value between any two of the above.

[0077] In the present invention, if the holding time of melt doping is less than 30 minutes, it may cause uneven dispersion of nanometal and insufficient combination with porous carbon, resulting in limited improvement in material performance; when the holding time is greater than 120 minutes, it may cause the already evenly dispersed nanometal to agglomerate again, and may also damage the porous carbon structure.

[0078] Preferably, the nano-metal includes one or more of nano-magnesium, nano-lithium, nano-nickel or nano-copper.

[0079] Preferably, the particle size of the nano metal is 1-5 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm or 5 μm, and any value between the above two.

[0080] In the present invention, nanometal with a particle size of 1-5 μm is used, which is relatively matched with the pore structure size of the porous carbon of the present invention. In the molten state, the nanometal can smoothly enter the pores of the porous carbon and be evenly distributed therein, forming a good composite structure with the porous carbon. This helps to give full play to the respective advantages of the nanometal and the porous carbon, improve the comprehensive performance of the material, and also simplifies the difficulty of process control in the preparation process and improves the preparation efficiency.

[0081] Preferably, during the passivation treatment, the passivation gas flow rate is 10-100 mL / min, for example, it can be 10 mL / min, 20 mL / min, 30 mL / min, 40 mL / min, 50 mL / min, 60 mL / min, 70 mL / min, 80 mL / min, 90 mL / min or 100 mL / min, and any point value between any two of the above.

[0082] Preferably, the passivation treatment time is 30-300 min, for example, 30 min, 60 min, 120 min, 180 min, 240 min or 300 min, and any value between any two of the above.

[0083] Preferably, the passivating gas comprises carbon dioxide and / or oxygen.

[0084] Preferably, the melt doping and passivation treatment are both performed in a tube furnace.

[0085] In a preferred embodiment of the present invention, the preparation method comprises the following steps: S1: phenyl resin: activator: cross-linking agent = 100: 1-5: 5-15, phenyl resin, activator, cross-linking agent are uniformly mixed and solidified at a temperature of 350-600 ° C for 1-6 hours, then the obtained material is pickled with 0.1 mol / L hydrochloric acid, vacuum dried at 80 ° C, and then a reducing mixed gas is introduced, and the reduction treatment is carried out at a flow rate of 100-500 mL / min for 1-10 hours to obtain an intermediate material; S2: The intermediate material is transferred to a tube furnace, nitrogen is introduced to exhaust the air in the tube, and then the temperature is raised to 1300-1500°C for high-temperature carbonization treatment for 1-6 hours, and then the temperature is lowered to 1000-1200°C, and water vapor is introduced at a flow rate of 100-500mL / min for 30-300min for activation treatment to obtain a porous carbon material; S3: Mix the porous carbon material and nanometal evenly at a mass ratio of porous carbon material: nanometal = 100:1-10, and transfer them to a tubular furnace. First, introduce nitrogen to expel the air in the tube, then heat to 800-1200°C to melt and keep warm for 0.5-2h. Then, introduce passivation gas and perform passivation treatment at a flow rate of 10-100mL / min for 30-300min to obtain metal-doped porous carbon.

[0086] According to a second aspect of the present invention, there is provided a metal-doped porous carbon obtained by the preparation method as described in the first aspect, wherein the metal-doped porous carbon comprises 1-5wt% of metal and 95-99wt% of porous carbon.

[0087] In the present invention, the metal is, for example, 1wt%, 2wt%, 3wt%, 4wt% or 5wt%, and any value between the above two. The porous carbon is, for example, 95wt%, 96wt%, 97wt%, 98wt% or 99wt%, and any value between the above two.

[0088] Preferably, the specific surface area of ​​the metal-doped porous carbon is 500-3000 m 2 / g, pore volume is 0.5-3.0cm 3 / g, pore size is 1-20nm, and powder resistivity is 0.1-1Ω·cm.

[0089] According to a third aspect of the present invention, there is provided an application of the metal-doped porous carbon as described in the second aspect in the field of secondary batteries.

[0090] Preferably, the secondary battery comprises a sodium battery or a lithium battery.

[0091] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0092] Example The present invention is further described in detail below in conjunction with the embodiments. It is to be understood that the specific embodiments described herein are only used to explain the relevant invention, rather than to limit the invention. It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other.

[0093] In the following examples, unless otherwise specified, all raw materials are commercially available products.

[0094] Example 1 A method for preparing metal-doped porous carbon comprises the following steps: S1: 100 g of phenylphenol formaldehyde resin, 3 g of zinc chloride and 10 g of 2-methylimidazole were uniformly mixed, and then cured at 500°C for 3 h. The obtained material was then added to 1000 g of 0.1 mol / L hydrochloric acid for pickling 3 times, and then vacuum dried at 80°C for 24 h. Then, a reducing mixed gas with a volume ratio of carbon monoxide and nitrogen of 3:10 was introduced, and the mixture was reduced at a flow rate of 300 mL / min for 300 min to obtain an intermediate material. S2: The intermediate material is transferred to a tube furnace, nitrogen is introduced to exhaust the air in the tube, and then the temperature is increased to 1400°C at a heating rate of 5°C / min, and high-temperature carbonization treatment is performed for 3 hours, and then the temperature is lowered to 1100°C, and water vapor is introduced at a flow rate of 300mL / min for 150 minutes for activation treatment to obtain porous carbon; S3: 100g of porous carbon and 5g of nano-lithium powder were mixed evenly, and transferred to a tubular furnace. After nitrogen was introduced to expel the air in the tube, the mixture was heated to 950°C to melt and kept warm for 1h. Then, carbon dioxide was introduced and the surface was passivated for 150min at a flow rate of 50mL / min to obtain metal-doped porous carbon.

[0095] Example 2 A method for preparing metal-doped porous carbon comprises the following steps: S1: 100 g of xylene formaldehyde resin, 1 g of zinc bromide, and 5 g of 4,5-dimethylimidazole were uniformly mixed, and then cured at 350°C for 6 h. The obtained material was then added to 1000 g of 0.1 mol / L hydrochloric acid for pickling three times, and then vacuum dried at 80°C for 24 h. A reducing mixed gas with a volume ratio of hydrogen and nitrogen of 1:10 was then introduced, and the reduction treatment was performed at a flow rate of 100 mL / min for 600 min to obtain an intermediate material. S2: The intermediate material is transferred to a tube furnace, nitrogen is introduced to exhaust the air in the tube, and then the temperature is increased to 1300°C at a heating rate of 1°C / min, and high-temperature carbonization treatment is performed for 6 hours, and then the temperature is lowered to 1000°C, and water vapor is introduced at a flow rate of 100mL / min for 300 minutes for activation treatment to obtain porous carbon; S3: 100g of porous carbon and 1g of nano-magnesium powder were mixed evenly, and transferred to a tubular furnace. After nitrogen was introduced to expel the air in the tube, the mixture was heated to 800°C for melting and kept warm for 2h. Then, oxygen was introduced and the surface was passivated for 300min at a flow rate of 10mL / min to obtain metal-doped porous carbon.

[0096] Example 3 A method for preparing metal-doped porous carbon comprises the following steps: S1: 100 g of phenol furfural resin, 5 g of zinc nitrate and 15 g of 4-formyl imidazole were uniformly mixed, and then cured at 600 ° C for 1 h. The obtained material was then added to 1000 g of 0.1 mol / L hydrochloric acid for pickling 3 times, and then vacuum dried at 80 ° C for 24 h. Then, a reducing mixed gas with a volume ratio of carbon monoxide and nitrogen of 5:10 was introduced, and the reduction treatment was carried out at a flow rate of 500 mL / min for 60 min to obtain an intermediate material; S2: The intermediate material is transferred to a tube furnace, nitrogen is introduced to exhaust the air in the tube, and then the temperature is increased to 1500°C at a heating rate of 10°C / min, and high-temperature carbonization treatment is performed for 1 hour, and then the temperature is lowered to 1200°C, and water vapor is introduced at a flow rate of 500mL / min for 30 minutes for activation treatment to obtain porous carbon; S3: 100g of porous carbon and 10g of nano-nickel were mixed evenly, and transferred to a tubular furnace. After nitrogen was introduced to exhaust the air in the tube, the mixture was heated to 1200°C to melt and kept warm for 0.5h. Then, oxygen was introduced and the surface was passivated at a flow rate of 100mL / min for 30min to obtain metal-doped porous carbon.

[0097] Example 4 The difference from Example 1 is that 1 g of zinc chloride and 5 g of 2-methylimidazole are used in step S1, and the rest is the same as Example 1.

[0098] Example 5 The difference from Example 1 is that 5 g of zinc chloride and 15 g of 2-methylimidazole are used in step S1, and the rest is the same as Example 1.

[0099] Example 6 The difference from Example 1 is that the curing treatment is performed at 350° C. for 6 hours in step S1 , and the other steps are the same as Example 1.

[0100] Example 7 The difference from Example 1 is that the curing treatment is performed at 600° C. for 1 hour in step S1 , and the rest is the same as Example 1.

[0101] Example 8 The difference from Example 1 is that the volume ratio of carbon monoxide to nitrogen in step S1 is 1:10, and the rest is the same as Example 1.

[0102] Example 9 The difference from Example 1 is that the volume ratio of carbon monoxide to nitrogen in step S1 is 5:10, and the rest is the same as Example 1.

[0103] Example 10 The difference from Example 1 is that the temperature of the high-temperature carbonization treatment in step S2 is 1300° C., and the time of the high-temperature carbonization treatment is 6 hours. The rest is the same as Example 1.

[0104] Embodiment 11 The difference from Example 1 is that the temperature of the high-temperature carbonization treatment in step S2 is 1500° C., and the time of the high-temperature carbonization treatment is 1 hour. The rest is the same as Example 1.

[0105] Example 12 The difference from Example 1 is that the activation treatment temperature in step S2 is 1000° C., and the rest is the same as Example 1.

[0106] Embodiment 13 The difference from Example 1 is that the activation treatment temperature in step S2 is 1200° C., and the rest is the same as Example 1.

[0107] Embodiment 14 The difference from Example 1 is that 1 g of nano lithium powder is used in step S3, and the rest is the same as Example 1.

[0108] Embodiment 15 The difference from Example 1 is that 10 g of nano lithium powder is used in step S3, and the rest is the same as Example 1.

[0109] Comparative Example 1 The difference from Example 1 is that nano lithium powder is not added in step S3, and the rest is the same as Example 1.

[0110] Comparative Example 2 The difference from Example 1 is that zinc chloride and 2-methylimidazole are not added in step S1, and the other steps are the same as Example 1.

[0111] Performance Testing 1. Scanning electron microscope (SEM) test: The SEM image of the metal-doped porous carbon prepared in Example 1 is as follows: Figure 1 As shown by Figure 1 It can be seen that the material has a granular structure with uniform size distribution and the particle size is between 5-10μm.

[0112] 2. Physical and chemical and button battery tests: 2.1 Physical and chemical performance test: The pore volume and pore size of the porous carbon obtained in Examples 1-15 and Comparative Examples 1-2 were tested with reference to the national standard GB / T-38949-2020 "Standard Particle Method for Determination of Porous Membrane Pore Size"; And according to the national standard GB / T-24533-2019 "Graphite for lithium-ion battery graphite negative electrode materials", its particle size D50, specific surface area and tap density are tested; The powder conductivity of each porous carbon material was tested using a four-probe tester; The above test results are shown in Table 1; The pressure-specific surface area method is used to test the compressive resistance of the material, that is, the compressive resistance of the material is determined by applying a certain pressure to cause a change in the specific surface area of ​​the material.

[0113] The test results are shown in Table 2.

[0114] 2.2 Button battery performance test: The metal-doped porous carbon corresponding to Examples 1-15 and Comparative Examples 1-2 was used as the negative electrode material for lithium-ion batteries to prepare button batteries according to the following method: Add binder, conductive agent and solvent to the corresponding metal-doped porous carbon, stir to make slurry, apply it on copper foil, dry and roll to obtain negative electrode sheet; the binder used is LA132, the conductive agent is SP (conductive carbon black), the solvent is NMP (N-methylpyrrolidone), the amount ratio of metal-doped porous carbon: SP: LA132: NMP is 80g: 15g: 15g: 300mL; the electrolyte is LiPF 6 The electrolyte solution has a concentration of 1 mol / L, wherein the solvent is a mixture of EC and DEC in a volume ratio of 1:1; the metal lithium sheet is the counter electrode, and the diaphragm is a polypropylene (PP) film.

[0115] Each button cell was assembled in an argon-filled glove box and then subjected to the following performance tests: Electrochemical performance test: The electrochemical performance was tested on Wuhan Blue Electric CT2001A battery tester, with a charge and discharge voltage range of 0.005V to 2.0V and a charge and discharge rate of 0.1C. The discharge specific capacity and initial efficiency of the corresponding button cell were tested. At the same time, the room temperature charging DCR and cycle performance test (0.1C / 0.1C, 100 weeks) of the corresponding button cell were tested. The diffusion coefficient of the material was tested by GITT. The test results are shown in Table 3.

[0116] Table 1 Physical and chemical properties of Examples 1-15 and Comparative Examples 1-2

[0117] Table 2 Button battery performance test

[0118] It can be seen from Table 1 and Table 2 that Examples 1-15 have low powder resistivity and high first efficiency. This is because the metal doping in the examples improves the electronic conductivity of the material, and the pore volume and pore size of the material are improved by adding a pore-forming agent to the resin, thereby increasing the specific surface area, improving the liquid absorption capacity of the material, and improving the diffusion coefficient of the material.

[0119] Table 3 Compression resistance test of Examples 1-15 and Comparative Examples 1-2

[0120] It can be seen from Table 3 that after the step pressure is applied, the specific surface area of ​​the embodiment material increases slightly, indicating that the material has strong compressive resistance under high pressure. The reason is that the embodiment material is doped with metal elements to enhance the compressive resistance of the material.

[0121] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing metal-doped porous carbon, characterized in that: The preparation method comprises the following steps: S1 first cures the phenyl resin, activator and cross-linking agent at 350-600°C, then acid washes, vacuum dries, and then introduces a reducing mixed gas for reduction treatment to obtain an intermediate material; S2, in an inert atmosphere, subjecting the intermediate material to a high-temperature carbonization treatment at 1300-1500° C., and then introducing water vapor for activation treatment to obtain porous carbon; S3: In an inert atmosphere, the porous carbon is melt-doped with nano-metal, and then passivated to obtain metal-doped porous carbon.

2. The preparation method according to claim 1, characterized in that The mass ratio of the phenyl resin, the activator and the cross-linking agent is 100:1-5:1-15, and the curing time is 1-6h; The phenyl resin includes one or more of phenylphenol formaldehyde resin, xylene formaldehyde resin, phenol furfural resin, benzoguanamine resin or resorcinol formaldehyde resin; The activator includes one or more of zinc chloride, zinc bromide and zinc nitrate; The cross-linking agent includes one or more of 2-methylimidazole, 4,5-dimethylimidazole, 4-formylimidazole, 2-propylimidazole or 2-phenylimidazole.

3. The preparation method according to claim 1, characterized in that: The reducing mixed gas includes reducing gas and nitrogen, the volume ratio of the reducing gas to nitrogen is 1-5:10, the flow rate of the reducing mixed gas is 100-500 mL / min, and the reduction treatment time is 1-10 h.

4. The preparation method according to claim 1, characterized in that: The heating rate of the high temperature carbonization treatment is 1-10°C / min, and the heat preservation time is 1-6h.

5. The preparation method according to claim 1, characterized in that: The temperature of the activation treatment is 1000-1200° C., the flow rate of water vapor is 100-500 mL / min, and the time of the activation treatment is 30-300 min.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The mass ratio of the porous carbon to the nano-metal is 100:1-10, the heating temperature of the melt doping is 800-1200° C., and the holding time of the melt doping is 30-120 min; The nano metal includes one or more of nano magnesium, nano lithium, nano nickel or nano copper, and the particle size of the nano metal is 1-5 μm.

7. The preparation method according to claim 6, characterized in that: During the passivation treatment, the passivation gas flow rate is 10-100 mL / min, the passivation treatment time is 30-300 min, and the passivation gas includes carbon dioxide and / or oxygen.

8. A metal-doped porous carbon prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The metal-doped porous carbon comprises 1-5 wt % of metal and 95-99 wt % of porous carbon.

9. The metal-doped porous carbon according to claim 8, characterized in that: The specific surface area of ​​the metal-doped porous carbon is 500-3000 m 2 / g, pore volume is 0.5-3.0cm 3 / g, pore size is 1-20nm, and powder resistivity is 0.1-1Ω·cm.

10. Use of the metal-doped porous carbon as claimed in claim 8 or 9 in the field of secondary batteries.

Citation Information

Patent Citations

  • High-rate porous carbon electrode material for super capacitor and preparation method

    CN104916447A

  • Porous carbon material for negative electrode of power lithium ion battery and preparation method thereof

    CN106299367A

  • Preparation method capable of weakening cracking of resin based porous carbon material

    CN107857264A

  • Metal atom-doped porous carbon nano composite material as well as a preparation method and application thereof

    CN109802124A

  • Porous hard carbon negative electrode material, preparation method thereof and sodium ion battery

    CN117228670A

Cited By

  • Lithium-doped porous carbon material, lithium-doped silicon-carbon composite material, preparation method and application thereof, and lithium ion battery

    CN119911904A

  • Porous carbon composite material and preparation method thereof

    CN120646829A